(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
A drip irrigation system was designed and installed at theDemonstration Farm, Faculty of Agriculture, University of Khartoum–Shambat, during the seasons 2001/02 and 2002/03 for the irrigation ofstrawberry. Irrigation treatments were drip irrigation at intervals of one,two and three days. These were compared with surface irrigation everysix days. The study included testing of the system design criteria namely,distribution efficiency, amount of water applied and effect of irrigationintervals on growth and yield of strawberry. The results showed that withthe drip system less water was used and high distribution efficiency(90.8%) was achieved at installation time, which decreased to 90.1% afterthe end of the second season. The water applied was only 25% of thevolume applied by furrow irrigation. Irrigation every day and every twodays resulted in greater vegetative and reproductive growth of strawberry,reflected in greater number of leaves, runners, flowers and fruits, withsignificantly (P  0.05) higher total yield than the other treatments.